2022
DOI: 10.1001/jamanetworkopen.2022.8031
|View full text |Cite
|
Sign up to set email alerts
|

Association of the 2020 US Presidential Election With Hospitalizations for Acute Cardiovascular Conditions

Abstract: This cohort study examines acute cardiovascular disease (CVD) hospitalizations following the 2020 US presidential election.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Previous research has demonstrated increases in poor health around the time of elections and political events including stress, anxiety, depression, high blood pressure, suicide, and cardiovascular conditions ( Anýž et al, 2019 ; Classen, 2009 ; Hagan et al, 2020 ; Hoyt et al, 2018 ; Hwang et al, 2022 ; Mefford et al, 2022 ; Nayak et al, 2021 ; Rosman et al, 2021 ). For example, the 2016 U.S. Presential election of Donald J. Trump was shown to be associated with significant reductions in sleep duration, increases in systolic and diastolic blood pressure, and clinically significant distress including intrusive thoughts and avoidance ( Anýž et al, 2019 ; Hagan et al, 2020 ; Hwang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated increases in poor health around the time of elections and political events including stress, anxiety, depression, high blood pressure, suicide, and cardiovascular conditions ( Anýž et al, 2019 ; Classen, 2009 ; Hagan et al, 2020 ; Hoyt et al, 2018 ; Hwang et al, 2022 ; Mefford et al, 2022 ; Nayak et al, 2021 ; Rosman et al, 2021 ). For example, the 2016 U.S. Presential election of Donald J. Trump was shown to be associated with significant reductions in sleep duration, increases in systolic and diastolic blood pressure, and clinically significant distress including intrusive thoughts and avoidance ( Anýž et al, 2019 ; Hagan et al, 2020 ; Hwang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research on the health effects of elections and associated partisanship has burgeoned in the last decade, first emerging after the 2008 U.S. Presidential election ( Classen, 2009 ; Stanton et al, 2010 ; Waismel-Manor et al, 2011 ). Since then, studies have documented a range of negative biobehavioral health consequences of elections including increases in poor health ( Fraser et al, 2022 ; Nelson, 2022 ), rising cortisol levels ( Stanton et al, 2010 ; Waismel-Manor et al, 2011 ), increases in the incidence of mental health conditions such as stress, depression, anxiety, sleep problems, and suicide ( Anýž et al, 2019 ; Classen, 2009 ; Hagan et al, 2020 ; Hoyt et al, 2018 ; Nayak et al, 2021 ), elevated blood pressure ( Hwang et al, 2022 ), increases in the onset of cardiac arrhythmias and acute cardiovascular disease ( Mefford et al, 2022 ; Rosman et al, 2021 ), and increases in all-cause mortality ( Maas & Lu, 2020 ). Given that issues such as immigration, foreign policy, welfare, taxes, racism, and marriage equality have historically been important during elections ( Dao, 2004 ; Newport, 2008 ; O’Connor, 2001 ; Yau, 2004 ), the impacts might be particularly salient for marginalized communities which tend to be deeply impacted by the policy effects of partisan changes.…”
Section: Introductionmentioning
confidence: 99%